PENGARUH MANAJEMEN PENDIDIKAN KARAKTER DAN BUDAYA RELIGIUS TERHADAP KESALEHAN SOSIAL SISWA DI MI NEGERI KABUPATEN GROBOGAN - Fahrudin Ali Nizar (Kopertais Wilayah X Jawa Tengah, 2021)
AbstractThe purpose of this research is to find out the influence of character education management and religious culture on the social piety of students at Madrasah Ibtidaiyah Negeri Grobogan Regency. This research is a field research using descriptive analytic research with a quantitative approach. The population in this study were all students at Madrasah Ibtidaiyah Negeri Grobogan Regency totaling 1365 people and the sample used was 310 students. Collecting data using questionnaires and data analysis techniques used with multiple regression analysis, t test, F test and coefficient of determination. The results of the study concluded that there is a significant influence on the management of character education and religious culture together on the social piety of students at Madrasah Ibtidaiyah Negeri Grobogan Regency, seen from the results of the F test, it is obtained that the F value is 26.486 from this test to determine the contribution contributed by the character education and religious culture management variables to the social piety of students calculated using R Square of 14.7%